A resource friendly authentication scheme for space–air–ground–sea integrated Maritime Communication Network. (15th April 2022) - Khan, Muhammad Asghar; Alzahrani, Bander A.; Barnawi, Ahmed; Al-Barakati, Abdullah; Irshad, Azeem; Chaudhry, Shehzad Ashraf
Abstract: Recently, the demand for a faster, low-latency, and full-coverage Maritime Communication Network (MCN) has gained attention as marine operations have increased substantially. Using modern information network technologies and integrating space, air, ground, and sea network segments, MCN may be able to offer worldwide coverage and diverse Quality-of-Service (QoS) provisioning. These network segments are expected to provide not only traditional communication services, but also processing, caching, sensing, and control capabilities when linked via Sixth Generation (6G) mobile networks. However, this development in infrastructure growth is subjected to new security and privacy concerns due to open links, moving nodes, and diverse collaborative algorithms. In this paper, we propose an improved and resource friendly authentication scheme for the space–air–ground–sea integrated maritime communication network using Elliptic Curve Cryptography (ECC). To validate the security hardness of the proposed scheme, formal security assessment method such as Random Oracle Model (ROM) is used. Finally, comparisons with relevant authentication schemes are provided in terms of computation and communication costs. The findings support the viability of the proposed scheme. Highlights: Proposed resource-friendly authentication for space–air–ground–sea integrated MCN. Employed ECC for smaller key size and equivalent security level. The formal ROM model is used for security verification. Comparisons with counterpart schemes is also provided. Proposed scheme provides better security-to-efficiency tradeoff.